Tolerance to Systemic Isotretinoin Therapy in Two Patients Using Highly Wettable Contact Lenses - Ayşegül Arman; D. Deniz Demirseren; Gulsen Akoglu (Case Reports in Ophthalmological Medicine)
Purpose. Numerous ocular side effects have been reported with the use of systemic isotretinoin therapy. Herein, we presented two contact lens user patients who did not have contact lens intolerance during systemic isotretinoin therapy. Methods. 25-year-old male and 20-year-old female patients with severe acne vulgaris who were using highly wettable silicone hydrogel contact lenses which increase tear film stability were examined. Tear film function tests including Schirmer tests and tear break up time (TBUT) test and ocular surface staining with fluorescein were done. Subjective ocular complaints were scored with ocular surface disease index (OSDI) questionnaire. Patients were followed up monthly and examinations were repeated at each visit. Results. Both patients completed the therapy after a cumulative dose of 140 mg/kg isotretinoin in 6 months. The OSDI score and tear film function tests before and after treatment were all within normal limits. Discussion. Highly wettable contact lenses that provide increase in the tear film stability may be used during systemic retinoid therapy under close followups. Although isotretinoin affects ocular glands, the differences between tolerances to this retinoid therapy need to be investigated in larger patient groups using contact lenses.